The Democratic Horizon of Emancipation: Interview with Maristella Svampa on the Crisis of the Progressive Cycle in Latin America (Alternautas, 2016)
Maristella Svampa is a sociologist and researcher at CONICET (National Technical and Scientific Research Council) at the University of La Plata. She is the author of a dozen books that have had a significant impact on the academic and public discussion of regional politics, social movements, and the function of the state in Latin America. Among her most recent books are Fifteen Myths and Realities of Transnational Mining in Argentina (Colectivo Ediciones Herramientas, 2011), Maldevelopment: Extractivism and Plunder in Argentina (co-written with Enrique Viale, Katz, 2014), and Latin American Debates: Indianism, Development, Dependency, and Populism (Edhasa, 2016). Over the course of the decade, Svampa’s critical work has constituted a sustained effort to understand the progressive actors of the region, as well as an inquiry into the geopolitical configuration at the intersection of state form and transnational capital.